The role of Klotho in energy metabolism - Razzaque, M. Shawkat (2012)
A disproportionate expansion of white adipose tissue and abnormal recruitment of adipogenic precursor cells can not only lead to obesity but also impair glucose metabolism, which are both common causes of insulin resistance and diabetes mellitus. The development of novel and effective therapeutic strategies to slow the progression of obesity, diabetes mellitus and their associated complications will require improved understanding of adipogenesis and glucose metabolism. Klotho might have a role in adipocyte maturation and systemic glucose metabolism. Klotho increases adipocyte differentiation in vitro, and mice that lack Klotho activity are lean owing to reduced white adipose tissue accumulation; moreover, mice that lack the Kl gene (which encodes Klotho) are resistant to obesity induced by a high-fat diet. Knockout of Kl in leptin-deficient Lep(ob/ob) mice reduces obesity and increases insulin sensitivity, which lowers blood glucose levels. Energy metabolism might also be influenced by Klotho. However, further studies are needed to explore the possibility that Klotho could be a novel therapeutic target to reduce obesity and related complications, and to determine whether and how Klotho might influence the regulation and function of a related protein, β-Klotho, which is also involved in energy metabolism.